The moderating effect of CEO incentives and ideology in shaping the association between ESG performance and financial success - Maria Cristina Dorobantu; Sanjay Bissessur (MAB)
Financial incentives and personal ideologies play a pivotal role in shaping firm outcomes. Analyzing data from North American firms between 2010 and 2019, our results show that ESG-aligned compensation is significantly associated with ESG performance, suggesting effective incentive structuring. We also find a positive relationship between improved ESG performance and enhanced financial returns, highlighting the economic benefits of sustainable practices. CEOs with pro-sustainability values can more effectively translate ESG objectives into financial returns. Conversely, the independence of the board of directors shows a limited effect, with firms with more independent boards displaying a slightly higher relationship between ESG performance and financial outcomes.